Physiological, biochemical, and transcriptional regulation in a leguminous forage Trifolium pratense L. responding to silver ions - Mo, Fan (Plant physiology and biochemistry : PPB, 2021)
Copyright © 2021 Elsevier Masson SAS. All rights reserved.